Influence of prosthesis type and material on the stress distribution in bone around implants: A 3-dimensional finite element analysis - Gökçe Meriç; Erkan Erkmen; Ahmet Kurt; Yahya Tunç; Atılım Eser (Elsevier, 2011)
Background/purpose: The design and materials of a prosthesis affect the loading of dental implants and deformation of the bone. The aim of the study was to evaluate the effects of prosthesis design and materials on the stress distribution of implant-supported prostheses. Materials and methods: A 3-dimensional finite element analysis method was selected to evaluate the stress distribution in the bone. Three different models were designed as follows: a 3-unit implant-supported fixed partial denture (FPD) composed of a metal framework and porcelain veneer with (M2) or without a cantilevered extension (M1) and an FPD composed of a fiber-reinforced composite (FRC) framework and a particulate composite veneer without a cantilevered extension (M3). In separate load cases, 300-N vertical, 150-N oblique, and 60-N horizontal forces were applied to the prostheses in the models. von Mises stress values in the cortical and cancellous bone were calculated. Results: In cortical bone, the highest von Mises stresses were noted in the M2 Model with a vertical load; whereas, higher stresses were observed in the M1 Model with horizontal and oblique loads. The lowest stress values were determined in the M3 Model for all loading conditions. In cancellous bone, decreased stress values were found with all 3 models under the applied loads. Conclusions: Prosthesis design and materials affect the load-transmission mechanism. Although additional experimental and clinical studies are needed, FRC FPDs can be considered a suitable alternative treatment choice for implant-supported prostheses. Within the limitations of the study, the 3-unit FPD supported by 2 implants with a cantilevered extension revealed acceptable stress distributions.